The Application of Quantum Teaching Learning Model on Derivative Function using Maple Software in Informatics Engineering of South Aceh Polytechnic - Sera Delta Tanjung; Ihsan Ihsan (Jurnal Inotera, 2019)
In the curriculum informatics engineering program of South Aceh Polytechnic, functiom derivative is taught in the second semester. The derivative function is a mathematics concept who does manipulation toward a function, thus the function slope can be obtained quantitatively on the slanted point. The derivative function material is one of the difficult material faced by the students. Accordingly, the implementation of a learning model is a good thing to create students' interest on the subject. And the media also use to support teaching and learning process as software maple. The purpose of this research is to find out the students’ results who have taught by quantum teaching and also maple on derivative function and the students who have taught by conventional method, and also to know the students' responses after taught by quantum teaching and software maple on derivative material. Experimental method is used in this research by designing pre-test and post-test and control groups. The population is all of the second semester informatics engineering's students at South Aceh Polytechnic where they divided into two classes. The technique in gaining data is using two tests, they are written and questionnaire test. The result of data is analyzed by T-test, and questionnaire is analyzed by calculating the average scores which have set by Likert-scale. Research found that t-score > t-table that is 2.41>1,69. This showed that, the students' score on derivative material taught by quantum teaching by adopting media maple is better than the students' score taught by conventional method at informatics engineering of South Aceh Polytechnic. As for the students' responses, gainned the average of a proposed statements is 3.52. According to the specified criterias, the researcher concludes that the students' responses toward the implementation of quantum teaching by software maple on derivative function is very positive.